(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
In this article there is given information about a great Uzbek poetess Zulfia as well as her famous work. The main topics of her works are referred which leading to a perfect and friendly lifestyle. She also wrote about love to motherland and suppose